Subhankar Banerjee, Lannan Chair and Professor of Art & Ecology, University of New Mexico - Subhankar Banerjee (Panorama, 2019)
Inuit artists such as Ashevak and Teevee have created works that celebrate local ecologies and multispecies relations, but also have offered significant portrayals of the disintegration of the ecological fabric and tattering of ecospiritual and ecosocial relations.